Canine Adenovirus 2: A Natural Choice for Brain Circuit Dissection - Lavoie, Andréanne; Liu, Bao-hua (Frontiers in Molecular Neuroscience, 2020)
Canine Adenovirus-2 (CAV) is a non-human pathogen that has been used in a variety of applications, from vaccines against more infectious strains of CAV to genetic vectors for treatment of neurological disorders. More recently, CAV has been engineered for brain circuit dissection and become a natural choice for neuroscientists due to its many beneficial properties. Specifically, as a reliable genetic vector with minimal immunogenic and cytotoxic reactivity, CAV has been used for the retrograde transduction of various types of projection neurons with genes of interest. Consequently, CAV is particularly useful when studying the anatomy and functions of long-range projections. Moreover, combining CAV with conditional expression and trans-synaptic tracing results in the ability to study circuits with cell- and/or projection-type specificity. Lastly, with the well documented knowledge of viral transduction, new innovations have been developed to increase the transduction efficiency of CAV and circumvent its tropism, demonstrating the potential of CAV for circuit analysis.